Kualitas Hidup Pasien Kanker Serviks Dalam Pelayanan Palliative Di RS Kanker Dharmais Jakarta Barat - Aliana Dewi; Ulfah Nuraini Karim; Erika Lubis; Sari Narulita (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Cervical cancer originating from the surface mucosa of the cervix or from within the canal. is one of the leading causes of death for women. This disease has a broad psychosocial impact on both patients and families, causing a decrease in quality of life. This study is to explore the meaning of quality of life of cervical cancer patients in palliative home care.Methods: This study uses an exploratory qualitative method with a phenomenological approach obtained from the description of the quality of life of cervical cancer patients. Participants in this study were determined by purposive sampling technique, namely patients with cervical cancer at stage III and stage IV, totaling 13 people, consisting of 8 main participants, namely cervical cancer patients and or patient companions (caregiver / patient's family) and 5 supporting participants. namely nurses and or doctors and psychologists. Collecting data in this study through in-depth interviews with the main participants and Focus Group Discussion (FGD) with supporting participants. The data analysis stage is divided into 2, namely the coding stage with NVivo 12 Plus software and the analysis stage using the Colaizzi's method. Results: Quality of Life Physical Domains include Activity, Pain, Sleep and Rest, Diet and Decreased sexual function, decreased libido. The psychological sub-themes experienced are self-image, life motivation, anxiety and depression, social isolation and loneliness. The social changes experienced are changes in social functions and changes in roles. The patient's quality of life and consequences were evaluated taking into account the cumulative effect globally. Multiple functional impairments and multiple low quality of life domains.  Conclusion: Palliative Homecare as a Key Component of Cervical Cancer Treatment. Various domains of quality of life are closely related to the accuracy of the information received on Palliative homecare services and encourage collaboration and partnerships when working with Palliative homecare services so that they are able to optimize Palliative homecare services.